1994
DOI: 10.1111/j.1699-0463.1994.tb05222.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal fibronectins in oral carcinomas:

Abstract: Different isoforms of fibronectin are derived from a single gene by alternative processing of the primary RNA transcript or by posttranslational modifications. We have previously demonstrated that an oncofetal fibronectin (FN) isoform derived by O‐glycosylation is highly associated with malignancy in breast and oral tumors. Another oncofetal FN isoform containing the ED‐B sequence is derived by alternative splicing, and FN containing ED‐B has been found to be a stromal marker of malignancies in various tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Mandel et al, 1994). In contrast to OSCC, breast and colon carcinomas display only focal oncofetal fibronectin deposits if at all Pujuguet et al, 1996).…”
Section: Ed-b Fibronectin Synthesis Indicates Tumour Stroma Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandel et al, 1994). In contrast to OSCC, breast and colon carcinomas display only focal oncofetal fibronectin deposits if at all Pujuguet et al, 1996).…”
Section: Ed-b Fibronectin Synthesis Indicates Tumour Stroma Recruitmentmentioning
confidence: 99%
“…Recent results have given rise to a new definition of laminin and fibronectin as molecule families (Mandel et al, 1994;Kosmehl et al, 1996). Laminin is a heterotrimeric molecule with an α, β and γ chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the generation of a mouse monoclonal antibody, BC-1, which proved to be a reliable and an easy tool to handle, has encouraged many to use it in clinical studies. 11,15,22 Thus, the aim of our work is to determine the value of this protein in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown almost similar staining results using three different, 5C10, FD-6 and BC1, monoclonal antibodies. 15,16 ED-B FN, also designated as oncofetal FN, due to its presence in fetal and tumor tissues but not in their normal counterparts. 17 Using IHC technique, numerous works have shown its expression in normal proliferative endometrium, chronic inflammatory diseases and ocular angiogenesis.…”
Section: Introductionmentioning
confidence: 99%